RANCANGAN INSTALASI LAMPU PENERANGAN JALAN UMUM DENGAN SISTEM KONTAKTOR DAN TIMER - Ery Gunawan; Eko Wahyono (Universitas Muhammadiyah Pekajangan Pekalongan, 2017)
Electricity is a form of energy that can not be seen, although the effect can be in the form of heat, magnetism, and chemical reactions. Mains voltage is the potential difference between two points in an electric circuit, and is expressed in units of volts. This quantity measures the potential energy of an electric field resulting in the flow of electricity in an electrical conductor. Electric current is basically a movement directly. Charge carriers can be electrons or ions. Electric current flows only in the material in which charge carriers available in sufficient quantity and free to move. Electric current is continuously flowing electrons in a conductor due to differences in the number of electrons is not the same, the unit of electric current is Ampere. Magnets or magnetic contactor switch is a switch that works by magnetism. This means that this switch works when there is a force magnetism when electrified. Magnet serves as towing and release contacts. Timer is an automatic switch to the working principles of a particular time and may be specified in accordance which we define when the light goes on and when the lights will off.if we want the lights on at 18.00 and off hours of 5:30 and did not depend on either a sunny or cloudy weather, thus saving the cost of street lighting Lighting accounts. MCB (Miniature Circuit Breaker) is a component in the installation of street lighting electric lamp that has a very important role. This component serves as a protection system in electrical installations in the event of overload and short circuit electric current (short circuit or short circuit). In the assembly according to the block diagram picture is, of KWH meters toward the contactor, and routed toward timerswitch, then the timer output is returned to the contactor as movers electromagnetic coil contactor coil, so that the output contactor working toward the MCB. Of the MCB to the lamp street lighting as well as a safety divider and lamp. On the results of testing that has been done, it can be concluded: contactor can work normally ranging from 100 volts voltage up to 250 volts. The timer can be set by pressing into and out of the lattice lattice, grating into life at the output is position 1, and the grating out is the off position at the output grating 1. Each represents 30 minutes for the timing. MCB 2 amps will experience a trip on the power of 600 watts at a voltage of 227 volts.